2022
DOI: 10.1101/2022.04.21.489104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure of the human LACTB filament reveals the mechanisms of assembly and membrane binding

Abstract: Mitochondria are complex organelles that play a central role in metabolism. Dynamic membrane-associated processes regulate mitochondrial morphology and biogenesis in response to cellular demand. In tumor cells, metabolic reprogramming requires active mitochondrial metabolism for providing key metabolites and building blocks for tumor growth and rapid proliferation. To counter this, the mitochondrial serine beta-lactamase-like protein (LACTB) alters mitochondrial lipid metabolism and potently inhibits the proli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…We confirmed the RNA-seq results by RT–PCR in two different cell lines (PEO4 and EFO27), which showed a common strong down-regulation of different EMT-related factors (SLUG, CD44, TGM2, WNT5A, INHBA, LAMA3, GLIPR1, SERPINE2) upon LACTB induction for 3 d ( Fig 5E ). LACTB was previously shown to be associated with lipids and/or lipid metabolism ( 27 Preprint , 28 , 29 , 30 , 31 , 32 ). This was supported by our own results where we showed that in breast cancer model, LACTB exerts its tumor suppressive effect through down-regulation of mitochondrial lipid–synthesizing enzyme phosphatidyl serine decarboxylase (PISD) which is partially responsible for the resulting breast cancer cell differentiation ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the RNA-seq results by RT–PCR in two different cell lines (PEO4 and EFO27), which showed a common strong down-regulation of different EMT-related factors (SLUG, CD44, TGM2, WNT5A, INHBA, LAMA3, GLIPR1, SERPINE2) upon LACTB induction for 3 d ( Fig 5E ). LACTB was previously shown to be associated with lipids and/or lipid metabolism ( 27 Preprint , 28 , 29 , 30 , 31 , 32 ). This was supported by our own results where we showed that in breast cancer model, LACTB exerts its tumor suppressive effect through down-regulation of mitochondrial lipid–synthesizing enzyme phosphatidyl serine decarboxylase (PISD) which is partially responsible for the resulting breast cancer cell differentiation ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…The connection of LACTB and lipid metabolism was further supported by studies in hepatocellular carcinoma where it was shown that LACTB expression influences the expression and activity of important enzymes involved in lipid metabolism (such as carnitine palmitoyltransferase 1A, acyl-coenzyme A dehydrogenase) (28). Furthermore, recent study by Bennett et al (2022) provides evidence that LACTB filaments can bind liposomes that closely mimic the lipid composition of mitochondrial inner membranes (28). We hypothesize that the interaction of LACTB polymers with inner mitochondrial membranes might modulate the presence and/or activity of proteins/enzymes embedded in this membrane (such as PISD).…”
Section: Discussionmentioning
confidence: 99%